Elizabeth Maldonado: capstone - Maldonado, Elizabeth, artist (Colorado State University. Libraries, 2025)
The artist's statement: Elizabeth Maldonado is a Colorado painter pursuing her BFA at Colorado State University. Her work explores the themes of memory, identity and nostalgia through the reimagining of notable Batman video game characters. She alters the original characters' faces to create new identities that resonate with her personal childhood memories. Her medium of acrylic paint allows her to focus on the fluidity of these changing characters. Her inspiration for her current series stems from the video games she played growing up and the notable characters that make them.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting